2022
DOI: 10.48550/arxiv.2210.03019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Analysis and Calibration of Low Cost Resistive and Capacitive Soil Moisture Sensor

Abstract: Soil moisture is an essential parameter in agriculture. It determines several environmental and agricultural activities such as climate change, drought prediction, irrigation, etc. Smart irrigation management requires continuous soil moisture monitoring to reduce unnecessary water usage. In recent times, the use of low-cost sensors is becoming popular among farmers for soil moisture monitoring. In this paper, a comparison of low-cost resistive and capacitive soil moisture sensors is demonstrated in two ways. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Because the land has water and vice versa [47]. On the other side, knowledge of the soil's moisture content can help farmers make less mistakes [48]. One of the elements that influences soil fertility is the amount of water in the soil [49].…”
Section: ) Soil Moisture Field Data Valuesmentioning
confidence: 99%
“…Because the land has water and vice versa [47]. On the other side, knowledge of the soil's moisture content can help farmers make less mistakes [48]. One of the elements that influences soil fertility is the amount of water in the soil [49].…”
Section: ) Soil Moisture Field Data Valuesmentioning
confidence: 99%
“…The latter are known to work at low frequencies, and measurements are affected by soil texture, temperature and salinity [22][23][24][25]. Extensive research has demonstrated that such sensors are not so prone to temperature and salinity factors if working in the soil temperature range 15-30 • C and for soils where soil solution electrical conductivity EC w is less than 10 dS/m [26]. However, as measurement frequency increases (around 50 MHz and above), this influence is reduced [27] (Meter Group, online technical note on soil moisture sensors).…”
Section: Introductionmentioning
confidence: 99%